Nambu-Poisson dynamics - Ibáñez, R.; de León, M.; Marrero, J.C.; de Diego, D.M. (Archives of Mechanics, 1998)
Several physical systems can be described by using multibrackets instead of the usual Poisson or Jacobi brackets. Starting with the original construction of Nambu we give a brief review on recent results on multibrackets on manifolds.